Nutrient balance of a commercial feedlot - S.Q. Jones; J.M. Ham; Joel M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2008)
The ability to develop nutrient balance for a livestock operation is important for maintaining a long-term sustainable production system and for compliance with current and future environmental regulations. Producers invest considerable financial resources in farm inputs, primarily feed and livestock. When animals leave the farm, they retain a portion of the feed nutrients they consumed, but the majority of consumed nutrients are excreted. Once excreted, certain compounds in the manure volatilize, which lowers the manure nutrient content and diminishes economic value of the manure as fertilizer. In addition, these volatile compounds can create air quality concerns. Operations designated as concentrated animal feeding operations must develop nutrient management plans to provide documentation that the manure produced will be applied at agronomic rates for environmental protection. Understanding the nutrient balance of a livestock operation is critical in developing whole-farm manure management plans. Objectives of this experiment were to determine the nutrient balance of a commercial feedlot and measure amounts of recoverable nitrogen and phosphorus from the feedlot pen surface.
Keywords: Cattlemen& #x27; s Day; 2008; Kansas Agricultural Experiment Station contribution; no. 08-212-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 995; Beef; Cattle; Nutrient balance; Nitrogen; Phosphorus